2019
DOI: 10.1002/adsc.201900621
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Incorporation Using Disulfanes as the Sulfur Atom Source Enabled Metal‐Free Heteroannulation of 1,7‐Enynes

Abstract: A new oxidative [2 + 2 + 1] heteroannulation of 1,7-enynes with disulfanes promoted by Et 3 N, producing 3,3a-dihydro-thieno[3,4-c]quinolin-4(5H)-ones, is described. This reaction is achieved by using equivalent amounts of 1,7-enynes, sulfur atoms (disulfanes), tert-butyl peroxybenzoate (TBPB) as an oxidant and Et 3 N as the base, and represents an unprecedented strategy to applications of disulfanes as sulfur atom sources in synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Because a variety of free radical precursors could provide highly active free radicals without the use of metal catalysts, the radical-mediated 1,n-enyne cyclization method attracted extensive attention . After that, the first example of using disulfanes as the sulfur atom sources for the synthesis of [3,4- c ]­quinolin-4­(5 H )-ones via the 1,7-enyne oxidative [2 + 2 + 1] heteroannulation reaction was successfully developed by Li′s group in 2019 (Scheme b) …”
Section: Introductionmentioning
confidence: 99%
“…Because a variety of free radical precursors could provide highly active free radicals without the use of metal catalysts, the radical-mediated 1,n-enyne cyclization method attracted extensive attention . After that, the first example of using disulfanes as the sulfur atom sources for the synthesis of [3,4- c ]­quinolin-4­(5 H )-ones via the 1,7-enyne oxidative [2 + 2 + 1] heteroannulation reaction was successfully developed by Li′s group in 2019 (Scheme b) …”
Section: Introductionmentioning
confidence: 99%
“…Recently, a radical‐mediated [2+2+n] strategy has proven to be powerful and efficient method for the construction of highly functionalized cyclic compounds from 1,n‐enynes, [16] in which, the [2+2+1] radical annulation showed terrific potential to synthesize fused ring compounds in a number of elegant studies (Scheme 1, Previous work). In these [2+2+1] radical annulation, oxidative cyclobutanone oximes, [17] 1,3‐dicarbonyl compounds, [18] 4‐methoxyanilines, [19] disulfides, [20] azidobenziodoxolone, [21] α ‐carbonyl alkyl bromides, [22] thiocyanates, [23] TMSN 3 , [24] DTBP, [25] alkyl nitriles or acetone, [26] α ‐bromo diethyl malonate, [27] alkylcarboxylic acids, [28] cycloalkanes, [29] and DCM [30] were usually driven as unary synthons. However, it could be inevitably found that all these reactions were almost invovled aniline‐linked 1,7‐enynes, while phenol‐linked 1,7‐enynes was very seldom used in this transformation due to their poor reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…108,109 O Fe(II) pode ser regenerado a partir da reação entre Fe(II) e H2O2. O radical carbamoíla é gerado a partir da formamida pela ação do radical hidroxila, [10][11][12][13] em seguida, esse radical ataca a dupla ligação carbono-carbono da unidade acrilamida gerando o radical terciário, que subsequentemente sofre ciclização com a tripla ligação carbono-carbono, [14][15][16][17][18][19][20][21][22][23] gerando o radical vinil II. A reação de recombinação dos radicais hidroxila e vinil II gera o enol III.…”
Section: Utilização De Micro-ondas Em Síntese Orgânicaunclassified
“…1 A obtenção de 2-quinolinonas a partir de 1,7-eninos já é bem conhecida. [14][15][16][17][18][19][20][21][22][23] No entanto, esse trabalho revela uma reação ultrarrápida de 10 segundos envolvendo múltiplas etapas de reação, como a abstração de hidrogênio para formar radicais carbamoíla e hidroxila, formação de 2quinolinonas, hidroxilação radicalar, epoxidação e abertura do anel de epóxido. Todas essas etapas levaram à formação de produtos isolados com diastereosseletividade definida.…”
Section: Conclusões E Perspectivasunclassified